Pojok Baca Islami sebagai Wujud Penguatan Literasi Keagamaan Anak di TPQ Hidayah Baitul Arfa melalui Pendekatan Asset-Based Community Development - Alpeny Julia Saputri; Khermarinah; Sherly Marselinda; Anisa Rahmadani; Fitri Rahma Nur Azizah; Khaheru Abdila (LKP KARYA PRIMA KURSUS, 2026)
Religious literacy is a crucial aspect in character building and strengthening children’s understanding of Islamic values. However, limited literacy facilities at TPQ Hidayah Baitul Arfa have resulted in relatively low reading activities of religious materials outside regular learning sessions. On the other hand, the TPQ has various assets that can be optimized, such as learning spaces, teaching staff, Community support, and Islamic book collections. This Community service program seeks to enhance children’s religious literacy through the establishment of an Islamic Reading Corner using the Asset-Based Community Development (ABCD) approach. The implementation method consists of four stages, namely discovery, dream, design, and destiny. The findings indicate that the Islamic Reading Corner was successfully established and actively utilized by students. The number of active readers increased from 15 to 38 students, the frequency of reading corner visits increased from 12 to 41 times per week, and the number of borrowed books increased from 8 to 27 books. In addition, the Societal Impact Index measurement showed a partner satisfaction level of 91.5%, categorized as very good. This program not only enhances children’s reading interest and religious literacy but also strengthens Community participation in supporting asset-Based religious education. Thus, the ABCD approach is proven effective in implementing sustainable literacy programs in TPQ environments.